ATMOSPHERES ON THE TERRESTRIAL PLANETS: CLUES TO ORIGIN AND EVOLUTION - Pepin R.O. (My University, 2006)
Earth, Venus and Mars reached their final sizes in the first 100 Myr or so of solar system history. For part of that time the growing planets and the materials forming them were immersed in the Sun-like gases of the solar nebula, and so one would expect that their early volatile inventories were acquired from the nebula. But the compositions of atmospheres presently on these planets are not solar, and therein lies a complex and fascinating story of physical and chemical evolution over the past 4.5 Ga. Records of physical processing survive most clearly in the chemically inert noble gases, and data on the elemental and isotopic abundances of these trace constituents, now from Mars and Venus as well as Earth, point to atmospheric histories punctuated by enormous inputs of energy from early astrophysical sources long since vanished. Observational and theoretical advances during the past 30 years underpin current evolutionary models in which primordial solar-like atmospheric gases are fractionated by gravitational escape, driven on Earth by a giant Moon-forming impact, on Mars by sputtering at high altitudes, and on all three planets by adsorption of intense ultraviolet radiation from the young Sun. Residual atmospheres left behind after these outflows to space are augmented by planetary degassing, including species generated in their interiors by radioactive decay. Interplay over time of these mechanisms for loss and gain of atmospheric gases can account for many of the details of contemporary noble gas distributions. These of course are just models. However they have predictive power for compositions as yet unmeasured, particularly on Venus, and the modeling assumptions are in principle testable by experiment or theory. The fundamental question of whether nature actually shaped the atmospheres in this way is still unanswered, but at least we have an outline of how it might have happened. © 2006 Elsevier B.V. All rights reserved.
Keywords: ATMOSPHERES; GRAVITATIONAL ESCAPE; TERRESTRIAL PLANETS